Answer:
simplify =36x−24y
factor =12(3x−2y)
Step-by-step explanation:
Let's simplify step-by-step.
4(5x−6y)+16x
Factor 4(5x−6y)+16x
36x−24y
Solve the following system using substitution:
{y + 2.3 = 0.45 x
{-2 y = -3.6
In the second equation, look to solve for y:
{y + 2.3 = 0.45 x
{-2 y = -3.6
-3.6 = -18/5:
-2 y = -18/5
Divide both sides by -2:
{y + 2.3 = 0.45 x
{y = 9/5
Substitute y = 9/5 into the first equation:
{4.1 = 0.45 x
{y = 9/5
In the first equation, look to solve for x:
{4.1 = 0.45 x
{y = 9/5
4.1 = 41/10 and 0.45 x = (9 x)/20:
41/10 = (9 x)/20
41/10 = (9 x)/20 is equivalent to (9 x)/20 = 41/10:
{(9 x)/20 = 41/10
{y = 9/5
Multiply both sides by 20/9:
Answer: {x = 82/9
{y = 9/5
Answer:
1. 4/5
2. 80%
Step-by-step explanation:
Answer:
v = 120
Step-by-step explanation:
If v is inversely proportional to square root of d, then we can write
= k
If v = 30 and d = 400, then
30(
) = k
k = 30(20) = 600
Now
= 600
If d = 25, then v
= 600
5v = 600
v = 120